Mitochondrial dynamics changes with age in an APPsw/PS1dE9 mouse model of Alzheimer's disease. Issue 4 (1st March 2017) - Xu, Lin-Lin; Shen, Yang; Wang, Xiao; Wei, Li-Fei; Wang, Ping; Yang, Hui; Wang, Cun-Fu; Xie, Zhao-Hong; Bi, Jian-Zhong
Abstract : Increasing research suggests that mitochondrial defects play a major role in Alzheimer's disease (AD) pathogenesis. We aimed to better understand changes in mitochondria with the development and progression of AD. We compared APPsw/PS1dE9 transgenic mice at 3, 6, 9, and 12 months old as an animal model of AD and age-matched C57BL/6 mice as controls. The learning ability and spatial memory ability of APPsw/PS1dE9 mice showed significant differences compared with controls until 9 and 12 months. Mitochondrial morphology was altered in hippocampus tissue of APPsw/PS1dE9 mice beginning from the third month. 'Medullary corpuscle', which is formed by the accumulation of a large amount of degenerative and fragmented mitochondria in neuropils, may be the characteristic change observed on electron microscopy at a late stage of AD. Moreover, levels of mitochondrial fusion proteins (optic atrophy 1 and mitofusin 2) and fission proteins (dynamin-related protein 1 and fission 1) were altered in transgenic mice compared with controls with progression of AD. We found increased levels of fission and fusion proteins in APP/PS1 mice at 3 months, indicating that the presence of abnormal mitochondrial dynamics may be events in early AD progression. Changes in mitochondrial preceded the onset of memory decline as measured by the modified Morris water maze test. Abnormal mitochondrial dynamics could be a marker for early diagnosis of AD and monitoring disease progression. Further research is needed to study the signaling pathways that govern mitochondrial fission/fusion in AD.